Adherence to Follow-up Care Guidelines for Breast Cancer Survivors in four Canadian provinces: a CanIMPACT study - McBride, Mary; Groome, Patti; Jiang, Li; Whitehead, Marlo; Li, Dongdong; Decker, Kathleen; Kendell, Cynthia; Winget, Marcy; Turner, Donna; Urquhart, Robin; Grunfeld, Eva (International Journal of Population Data Science, 2018)
Introduction Breast cancer survivors are at risk for late and ongoing problems including cancer recurrence and late effects of treatment. Lack of access to quality follow-up care may affect later mortality, morbidity, and quality of life. This study examines variation in utilization of guideline-based follow-up care separately for four Canadian provinces. Objectives and Approach For our retrospective population-based cohort study of breast cancer survivors diagnosed from 2007 to 2010 in British Columbia (BC), 2007-2011 in Manitoba (MB), 2007-2010 in Ontario (ON), and 2007-2012 in Nova Scotia (NS), we linked provincial cancer registries, clinical and health administrative databases, and followed cases alive at 30 months post-diagnosis to five years from diagnosis. For each province, we calculated percent adherence, overuse, and underuse of recommended follow-up care, including surveillance for recurrent and new cancer, surveillance for late effects, and general preventive care. We also examined variation among provinces and over time. Results Survivor numbers were 23,700 (ON), 9493 (BC), 2688 (MB), and 2735 (NS). Annual oncologist visit guideline compliance varied provincially (e.g. Year 2 ON=32.7%, BC=15.0%). For most provinces and follow-up years, the majority of survivors had fewer oncologist visits than recommended. However, survivors had additional annual breast cancer-related visits to a primary care provider. Surveillance breast imaging guideline compliance was high (e.g. Year 2, ON=81.1%, MB=72.0%, NS=52.8%, BC =49.7%), with rates declining in ON and MB (to approximately 64%), but increasing in NS and BC (to approximately 58%) by Year 5. Overuse of breast imaging was identified in NS (9.1%-20.7% overuse in follow-up years 2-5). As per the guideline, 72.9%-79.7% (Years 2-5) of BC survivors had no imaging for metastastic disease, highest among all provinces. Conclusion/Implications Provincial and temporal variations in guideline adherence were identified. Patterns differed by guideline, and both overuse and underuse were observed. These results point to opportunities to improve survivor care and efficiencies in care delivery. In particular, regular care with a primary care physician has been shown to improve follow-up care.